Singaporean parents’ perspectives and experiences on raising a child with autism - Chong, Jessica Hui Xian (2017)
Having been identified as having Autism instantly hurls one into a sea of stereotypes and preconceived notions entailing discriminatory treatment. Caregivers, usually parents, are at the receiving end as they take on a larger role through the transitional journey of self-discovery alongside their child with ASD who may be highly dependent for the rest of their lives. Analysing the lived experiences of parents allows us to uncover, albeit increased efforts on improvement, the medical interventions, social stigma and double-edged discourses that surrounds Autism in Singapore. This study seeks to address how parents of children with Autism negotiate around the available resources provided by the state and voluntary welfare organizations. Findings in this study draws on medical and social models of disability, and follows through the different facets of their life encounters, dwelling on society’s role in disabling Autism. Inclusiveness is not simply cultivated through top-down approaches, but rather over-riding the negative mindsets through interactions and education. Only then can one envision a society, which prides itself on equality of opportunity and capability.